Understanding Conservation Agriculture in terms of Knowledge, Perception and Application (Indian Journal of Extension Education, 2022)
Depleting natural resources, environmental pollution and climate change are the three major factors of concern simmering up with contemporary global agriculture. Conservation agriculture (CA) is being flagged up as a sustainable adaptation mechanism. Adoption of CA depends upon ecological as well as, farmers’ level of perception, knowledge acquisition, and decision-making process. The present study was taken place in West Bengal covering both the new alluvial zone (NAZ) and terai zones (TZ) following snowballing sampling method during 2018-21. A total of 65 farm households were surveyed considering 57 different social-ecological factors operating across CA farms. The study elucidated that farmers’ perception of energy, climate change perception, formal education, land fragmentation, gender ratio, irrigated area, dietary diversity, and family size came up as strong determinants of their level of knowledge of CA. Understanding and measuring the complexity of social knowledge is essential for sustainable management, with consequences for problem-solving, mutual aid, and decision-making.